Hot rolling roll outer layer material, and, producing method thereof, as well as, hot rolling composite roll

By optimizing the chemical composition and grain structure of the hot-rolled coil, ensuring the area ratio of carbide is between 6.0-18.0%, the problem of insufficient seizure resistance and slip resistance of existing hot-rolled coils in rough rolling stations is solved, and excellent seizure resistance and slip resistance during the rolling process is achieved, improving production efficiency and product quality.

JP2025058879AActive Publication Date: 2025-04-09JFE STEEL CORP
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2024094124
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-28
Filing Date
2024-06-11
Publication Date
2025-04-09
Estimated Expiration
2044-06-11

AI Technical Summary

Technical Problem

When existing hot-rolled coils are used in rough rolling stations, seizure resistance and slip resistance are insufficient, resulting in slip and seizure problems easily occur during the rolling process, affecting product quality and production efficiency.

Method used

By optimizing the chemical composition and grain structure of the hot-rolled coil, the area ratio of carbides is ensured to be between 6.0-18.0%, the area ratio of Mo and W is between 0.6-4.0, the content of C is between 1.1-2.5%, the content of Mo and W is between 2.5-18.0%, the content of V and Cr is between 1.5-6.5%, and the content of P and S is between 0.01-0.08% and 0.001-0.050%. The hot-rolled coil is prepared by a cyclone casting process.

Benefits of technology

The excellent seizure resistance and slip resistance of hot-rolled coils during the rolling process are achieved, extending the service life of coils and rolling tools, and improving the production efficiency and product quality of hot-rolled steel plates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025058879000003
    Figure 2025058879000003
  • Figure 2025058879000004
    Figure 2025058879000004
  • Figure 2025058879000005
    Figure 2025058879000005
Patent Text Reader

Abstract

To provide a hot rolling roll outer layer material excellent in seizure resistance and slip resistance, and, a producing method thereof, as well as, a hot rolling composite roll.SOLUTION: In terms of mass%, a composition includes C: 1.1-2.5%, Si: 0.1-3.5%, Mn: 0.1-3.5%, Ni: 0.5-6.5%, Cr: 1.5-6.5%, Mo: 2.5-18.0%, V: 1.5-6.5%, W: 0.5-3.5%, P: 0.01-0.08%, S: 0.001-0.050%, with the balance being Fe and unavoidable impurities. The contents of Cr, Mo, V, and W satisfy formula (1), and the contents of C, Mo, and W satisfy formula (2), an area ratio of all precipitated carbides is 6.0-18.0%, and the area ratio of precipitated M2C type carbides is 1.0-8.0%, the relationship between the area ratio of all precipitated carbides and the area ratio of precipitated M2C type carbides satisfies formula (3).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an outer layer material for a hot rolling roll, a manufacturing method thereof, and a composite roll for hot rolling. [Background technology]

[0002] In recent years, the demand for high-quality steel sheets, such as high-tensile steel sheets, stainless steel sheets, and electrical steel sheets, has been increasing, and accordingly, there is a demand for improvements in hot rolling technology and productivity for producing the above-mentioned steel sheets. In addition, there is a strong demand for improvements in the properties, such as wear resistance, seizure resistance, and slip resistance, of hot rolling rolls used in hot rolling equipment for producing steel sheets.

[0003] Currently, hot rolling rolls in use include HiCr cast steel rolls incorporating Cr-based M7C3-type carbides, and high-speed steel rolls based on high-speed steel, a type of tool steel, containing carbide-forming elements such as V, Cr, Mo, and W and incorporating large amounts of hard carbides such as V-based MC-type carbides, Mo, W-based M2C-type carbides, and Cr-based M7C3-type carbides. Here, the above-mentioned M means a metal element that forms carbides.

[0004] In addition, in the finishing rear stands of hot rolling equipment, there is a possibility of a squeezing accident in which the steel sheet becomes multiple and gets caught between the upper and lower rolls. When a squeezing accident occurs, a part of the steel sheet seizes on the roll, and the part of the steel sheet that is stuck to the roll is strongly pressed down between the backup roll and the work roll. This may cause squeezing cracks in the work roll. In order to reduce the occurrence of cracks due to squeezing accidents, it is considered important to improve the seizure resistance of the work roll and suppress the seizure of the steel sheet. For this reason, Ni grain rolls, which have excellent seizure resistance and crystallize graphite as a solid lubricant, are used in the finishing rear stands.

[0005] On the other hand, since graphite reduces wear resistance, high-speed steel rolls that do not crystallize graphite are sometimes used in the finishing rear stands from the viewpoint of rolling efficiency. However, high-speed steel rolls have inferior seizure resistance to Ni-grain rolls. Therefore, various technologies have been proposed to improve the seizure resistance of high-speed steel rolls.

[0006] For example, Patent Document 1 proposes a composite roll for hot rolling, which contains one or more of C: 0.8-4.0%, Si: 0.2-2.0%, Mn: 0.2-2.0%, Cr: 3.0-15%, V: 3.0-15%, one or two of Mo and W: ≧2%, and Mo+0.5W: ≧6.1%, or further contains one or more of Ni: 0.2-5%, Co: 0.5-10%, Nb: 0.50-5.0%, and one or more of Al, Ti, and Zr: ≦0.5%, and the metal structure of the outer layer material has carbides with an area ratio of 5-30%, and the distribution of each carbide is such that the average gap between adjacent carbides is 20 μm or less. This allows the appropriate amount of granular carbide to be finely dispersed with small gaps between adjacent carbides, resulting in a composite roll for hot rolling with improved slip resistance and seizure resistance.

[0007] Patent Document 2 proposes a centrifugally cast hot rolling composite roll, which contains 1-3% C, 0.4-3% Si, 0.3-3% Mn, 1-5% Ni, 2-7% Cr, 3-8% Mo, 3-7% V, and 0.01-0.12% B, with the balance being Fe and unavoidable impurities, and satisfies the relationship expressed by Cr / (Mo+0.5W)<-2 / 3[C-0.2(V+1.19Nb)]+11 / 6 (wherein W and Nb, which are optional components, are not contained, W=0 and Nb=0). It also contains 1-15% MC type carbide, 0.5-20% carboboride, and 0.5-2.0% Mo type carbide by area ratio. It is said that the generated carboboride improves seizure resistance.

[0008] In Patent Document 3, the alloy contains C: 1.3 to 2.8%, Si: 0.3 to 1.8%, Mn: 0.3 to 2.5%, Ni: 0 to 6.5%, Cr: 1 to 10%, Mo: 0.9 to 6%, W: 0 to 8%, V: 0.5 to 6%, Nb: 0 to 3%, and B: 0% or more and less than 0.01%, with the balance being Fe and unavoidable impurities, and 1000≦1177-52C+14Si-11Mn A rolling roll outer layer material has been proposed, which has a chemical composition that satisfies +6.8Cr+1W+0.65Mo+12V+15Nb≦1115 and 5≦Cr+Mo+0.5W+V+1.2Nb≦15 (where C, Si, Mn, Cr, W, Mo, V and Nb indicate the mass% of each element), contains eutectic carbides, and has a structure that does not contain graphite. It is said that the lowest solidification heat generation start temperature among multiple solidification heat generation start temperatures obtained by differential thermal analysis is preferably 1100°C or less. As a result, when the rolling roll encounters a squeezing accident, the eutectic carbide with a low melting point melts due to frictional heat between the rolled material and the outer layer surface, improving the lubrication between the rolled material and the roll outer layer, and improving the seizure resistance. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] JP 2004-255457 A [Patent Document 2] International Publication No. 2015 / 045984 [Patent Document 3] International Publication No. 2017 / 170570 Summary of the Invention [Problem to be solved by the invention]

[0010] It is presumed that the seizure resistance of the high speed steel roll is better when the area ratio of the base of the high speed steel roll that causes metal-metal contact is smaller, that is, when the area ratio of the crystallized carbides is higher. On the other hand, when the area ratio of the crystallized carbides is higher, the surface roughness of the high speed steel roll is smaller, and slippage may occur easily during rolling. The hot rolling rolls described in Patent Documents 1 to 3 are suitable for rolls for finishing rolling stands where squeezing accidents occur and seizure is likely to occur even when rolling ordinary steel, and the seizure resistance and slippage resistance in such finishing rolling stands are improved. However, when the hot rolling rolls described in Patent Documents 1 to 3 are used in a rough rolling stand, both the seizure resistance and the slippage resistance, or either one of them, may be insufficient. That is, the hot rolling rolls described in Patent Documents 1 to 3 are mainly used as rolls for finishing rolling stands, and have a higher area ratio of crystallized carbides than hot rolling rolls conventionally used in rough rolling stands. Therefore, when the hot rolling rolls described in Patent Documents 1 to 3 are used in a rough rolling stand, slippage may occur easily. In addition, among the hot rolling rolls manufactured with the component ratios described in Patent Documents 1 to 3, in the hot rolling rolls having a low area ratio of crystallized carbides, the generation ratio of each type of crystallized carbide is not appropriate. Therefore, when this is used in a rough rolling stand, the seizure resistance may be insufficient. As a result, when the hot rolling rolls described in Patent Documents 1 to 3 are used in a rough rolling stand, both the seizure resistance and the slip resistance, or either one of them, may be insufficient.

[0011] The present invention has been made to solve the above-mentioned problems, and an object of the present invention is to provide a hot rolling roll outer layer material having excellent seizure resistance and excellent slip resistance, a manufacturing method thereof, and a hot rolling composite roll.

[0012] Here, "excellent seizure resistance" means that the average seizure area ratio measured by a drop weight frictional thermal shock test described later is 42.0% or less. The drop weight frictional thermal shock test will be described in the examples described later.

[0013] In addition, "excellent slip resistance" means that the ratio of the friction coefficient in the first test to the friction coefficient in the fifth test (μ5th / μ1st) measured by a hot rolling wear test described later is 0.80 or more. The hot rolling wear test will be described in the examples described later. [Means for solving the problem]

[0014] In order to solve the above-mentioned problems, the present inventors have investigated in detail the crystallized carbides, chemical components (composition), seizure area ratio, and friction coefficient during testing of hot rolling rolls. As a result, they have found that by optimizing the chemical components so that the amount of crystallized carbides falls within a specific range, and by optimizing the amount of Mo- and W-based crystallized M2C-type carbides, both the seizure resistance and the slip resistance can be improved.

[0015] The present invention has been completed based on these findings and further investigations. That is, the gist of the present invention is as follows. [1] The composition contains, by mass%, C: 1.1-2.5%, Si: 0.1-3.5%, Mn: 0.1-3.5%, Ni: 0.5-6.5%, Cr: 1.5-6.5%, Mo: 2.5-18.0%, V: 1.5-6.5%, W: 0.5-3.5%, P: 0.01-0.08%, S: 0.001-0.050%, and the remainder is Fe and unavoidable impurities. the contents of Cr, Mo, V and W satisfy the following formula (1), the contents of C, Mo and W satisfy the following formula (2), the area ratio of all crystallized carbides is 6.0 to 18.0%, the area ratio of crystallized M2C type carbides is 1.0 to 8.0%, and the relationship between the area ratio of all crystallized carbides and the area ratio of crystallized M2C type carbides satisfies the following formula (3). 0.6≦([%Mo]+[%W]) / ([%V]+[%Cr])≦4.0 (1) 1.0≦[%C]×([%Mo] / [%W])≦15.0 (2) 0.10≦Crystallized M2C type carbide area ratio (%) / total crystallized carbide area ratio (%)≦0.60 (3) In formula (1) and formula (2), [%C], [%Cr], [%Mo], [%V], and [%W] are the contents (mass%) of each element. [2] A method for producing an outer layer material for a hot rolling roll as described in [1], wherein a mold is rotated while pouring molten metal of the outer layer material having the above-mentioned component composition, thereby generating centrifugal force in the molten metal poured into the mold, and the molten metal is brought into close contact with the mold by the centrifugal force, thereby satisfying the following formula (4) when centrifugal casting the outer layer material for a hot rolling roll. 0.3℃ / sec≦ΔT(Pouring temperature ℃-Liquidus temperature ℃) / Pouring time sec≦5.0℃ / sec (4) [3] A composite roll for hot rolling having a two-layer structure of an outer layer and an inner layer, or a three-layer structure of an outer layer, an intermediate layer and an inner layer, wherein the outer layer is made of the outer layer material for hot rolling roll according to [1]. Effect of the Invention

[0016] According to the present invention, it is possible to obtain a hot rolling roll outer layer material having excellent galling resistance and excellent slip resistance, a manufacturing method thereof, and a hot rolling composite roll. As a result, it is possible to improve the life of the hot rolling roll outer layer material and the hot rolling roll, and accordingly, it is possible to improve the productivity of hot rolled steel sheets manufactured using the hot rolling roll outer layer material and the hot rolling roll. [Brief description of the drawings]

[0017] [Figure 1] FIG. 2 is a diagram for explaining the position at which test pieces for hot rolling wear testing were taken from a ring-shaped test material. [Diagram 2] FIG. 1 is a diagram showing an example of a hot rolling wear tester. [Diagram 3] FIG. 1 is a diagram showing an example of a drop weight type friction thermal shock tester. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] Hereinafter, an embodiment of the present invention will be described. Note that the following description shows an example of an embodiment of the present invention, and the present invention is not limited to the following embodiment.

[0019] The hot rolling roll outer layer material of the present invention is manufactured by centrifugal casting and can be used as a ring roll or sleeve roll as it is. Alternatively, the hot rolling roll outer layer material of the present invention can be used as the outer layer (outer layer material) of a hot rolling composite roll suitable for a hot rough rolling stand. In the centrifugal casting method, a mold is rotated while pouring the molten metal of the hot rolling roll outer layer material of the present invention, thereby generating a centrifugal force in the molten metal poured into the mold, and the molten metal is adhered to the inner wall surface of the mold by the centrifugal force, thereby centrifugal casting the hot rolling roll outer layer material.

[0020] The hot rolling composite roll of the present invention may have a two-layer structure of an outer layer (the hot rolling roll outer layer material of the present invention) and an inner layer welded and integrated with the outer layer. Alternatively, the hot rolling composite roll of the present invention may have a three-layer structure with an intermediate layer provided between the outer layer and the inner layer. In the three-layer structure hot rolling composite roll, the intermediate layer is welded and integrated with the outer layer, and the inner layer is welded and integrated with the intermediate layer. In the present invention, the composition of the intermediate layer is not particularly limited, but it is preferably a high carbon material with C: 1.5 to 3.0 mass %.

[0021] (Composition of outer layer material for hot rolling rolls) First, the reasons for limiting the composition of the outer layer material for hot rolling rolls (hereinafter, sometimes simply referred to as "outer layer material") of the present invention will be described. Hereinafter, unless otherwise specified, "mass%" will be simply referred to as "%".

[0022] C: 1.1-2.5% C combines with V, Cr, Mo, W, etc. to form hard crystallized carbides, thereby reducing metal-metal contact between the rolled material and the base structure of the roll material. Therefore, it contributes to improving the seizure resistance of the outer layer material. Here, examples of hard crystallized carbides include MC type carbides, M2C type carbides, and M7C3 type carbides. C also has the effect of dissolving in the base and increasing the hardness of the base by solid solution strengthening. If the C content is less than 1.1%, the amount of crystallized carbides is insufficient, and excellent seizure resistance cannot be obtained. On the other hand, if the C content exceeds 2.5%, excessive crystallized carbides are generated, and the hardness becomes too high, which reduces the surface roughness of the outer layer material, reduces the friction coefficient, and makes it easier to slip.

[0023] Therefore, the C content is limited to 1.1% or more and 2.5% or less. The C content is preferably 1.2% or more, and more preferably 1.4% or more. The C content is preferably 2.4% or less, and more preferably 2.2% or less. The C content is preferably 1.2% or more and 2.4% or less, and more preferably 1.4% or more and 2.2% or less.

[0024] Silicon: 0.1 to 3.5% Si acts as a deoxidizer in the molten metal, improves the fluidity of the molten metal, and has the effect of preventing casting defects. If the Si content is less than 0.1%, the deoxidizing effect is insufficient. On the other hand, if the Si content exceeds 3.5%, the deoxidizing effect is saturated. Therefore, the Si content is limited to 0.1% or more and 3.5% or less. The Si content is preferably 0.2% or more, and more preferably 0.4% or more. The Si content is preferably 3.2% or less, and more preferably 3.0% or less. The Si content is preferably 0.2% or more and 3.2% or less, and more preferably 0.4% or more and 3.0% or less.

[0025] Mn: 0.1-3.5% Mn has the effect of fixing S, which has an adverse effect on products, as MnS and removing it. If the Mn content is less than 0.1%, the effect of fixing S as MnS is not observed. On the other hand, if the Mn content exceeds 3.5%, this effect saturates. Therefore, the Mn content is limited to 0.1% or more and 3.5% or less. The Mn content is preferably 0.2% or more, and more preferably 0.4% or more. In addition, the Mn content is preferably 3.2% or less, and more preferably 3.0% or less. The Mn content is preferably 0.2% or more and 3.2% or less, and more preferably 0.4% or more and 3.0% or less.

[0026] Ni: 0.5-6.5% Ni is an element that improves the hardenability of the matrix, and has the effect of improving the matrix hardness. If the Ni content is less than 0.5%, the effect of improving the matrix hardness is insufficient. On the other hand, if the Ni content exceeds 6.5%, the residual austenite is promoted, so that the hardness decreases, the seizure area increases, and the seizure resistance decreases. Therefore, the Ni content is limited to 0.5% or more and 6.5% or less. The Ni content is preferably 1.0% or more, and more preferably 1.5% or more. The Ni content is preferably 5.0% or less, and more preferably 4.0% or less. The Ni content is preferably 1.0% or more and 5.0% or less, and more preferably 1.5% or more and 4.0% or less.

[0027] Cr: 1.5~6.5% Cr is a carbide-forming element and combines with C to form M7C3-type carbides. M7C3-type carbides reduce metal-metal contact between the roll matrix and the rolled material. Therefore, it has the effect of improving seizure resistance. If the Cr content is less than 1.5%, the amount of M7C3-type carbides is insufficient, and seizure resistance decreases. On the other hand, if the Cr content exceeds 6.5%, coarse M7C3-type carbides are generated, the surface roughness of the outer layer material becomes smaller, the friction coefficient decreases, and slippage becomes more likely to occur. In addition, cracks are more likely to occur due to the generation of coarse M7C3-type carbides with low toughness. Therefore, the Cr content is limited to 1.5% or more and 6.5% or less. The Cr content is preferably 2.5% or more, more preferably 3.0% or more. The Cr content is also preferably 6.0% or less, more preferably 5.5% or less. The Cr content is preferably 2.5% or more and 6.0% or less, and more preferably 3.0% or more and 5.5% or less.

[0028] Mo: 2.5-18.0% Mo is a carbide-forming element, and combines with C to form M2C-type carbides. M2C-type carbides are crystallized carbides that are harder than M7C3-type carbides, and are crystallized in a planar and lamellar shape, and further have the effect of improving seizure resistance. If the Mo content is less than 2.5%, the amount of M2C-type carbides is insufficient, and the effect of improving seizure resistance is insufficient. On the other hand, if the Mo content exceeds 18.0%, coarse lamellar M2C-type carbides with low toughness are generated, and cracks caused by the M2C-type carbides are likely to occur. Therefore, the Mo content is limited to 2.5% or more and 18.0% or less. The Mo content is preferably 3.0% or more, and more preferably 3.5% or more. The Mo content is preferably 16.0% or less, and more preferably 15.0% or less. The Mo content is preferably 3.0% or more and 16.0% or less, and more preferably 3.5% or more and 15.0% or less.

[0029] V: 1.5-6.5% V is a carbide-forming element and combines with C to form MC-type carbides. MC-type carbides have a Vickers hardness of about 2800 Hv. Like other crystallized carbides, MC-type carbides also reduce metal-metal contact between the roll matrix and the rolled material. Therefore, they have the effect of improving seizure resistance. If the V content is less than 1.5%, the amount of MC-type carbides is insufficient, and the effect of improving seizure resistance is insufficient. On the other hand, if the V content exceeds 6.5%, VC (VC means vanadium carbide, a type of MC-type carbide) which has a smaller specific gravity than molten iron is concentrated on the inside of the outer layer material (note that in the case of a composite roll described later, it is the "outer layer". The same applies hereafter) due to the centrifugal force during centrifugal casting, and segregation occurs. In this way, VC with low toughness accumulates on the inside of the outer layer material, making it easier for cracks to occur. Therefore, the V content is limited to 1.5% to 6.5%. The V content is preferably 2.0% or more, and more preferably 2.5% or more. The V content is preferably 6.0% or less, and more preferably 5.5% or less. The V content is preferably 2.0% or more and 6.0% or less, and more preferably 2.5% or more and 5.5% or less.

[0030] W: 0.5-3.5% W is a carbide-forming element, and like Mo, it combines with C to form hard crystallized carbides such as hard M2C carbides, and has the effect of improving seizure resistance. If the W content is less than 0.5%, the effect is insufficient and seizure resistance is deteriorated. On the other hand, if the W content exceeds 3.5%, coarse M2C carbides are formed, and seizure resistance is rather deteriorated. Therefore, the W content is limited to 0.5% or more and 3.5% or less. The W content is preferably 0.6% or more, and more preferably 0.8% or more. In addition, the W content is preferably 3.2% or less, and more preferably 3.0% or less. The W content is preferably 0.6% or more and 3.2% or less, and more preferably 0.8% or more and 3.0% or less. The W content is preferably 0.6% or more and 3.2% or less, and more preferably 0.8% or more and 3.0% or less.

[0031] P: 0.01-0.08% It has been believed that P is mixed in during the roll manufacturing process and reduces mechanical properties, but the inventors have made it clear through extensive research that the inclusion of a small amount of P has the effect of improving seizure resistance. If the P content is less than 0.01%, the effect of improving seizure resistance is insufficient. On the other hand, if the P content exceeds 0.08%, the mechanical properties deteriorate. Therefore, the P content is limited to 0.01% or more and 0.08% or less. The P content is preferably 0.02% or more and 0.06% or less.

[0032] S: 0.001 to 0.050% S is usually treated as a harmful element in iron-based alloys and its content is limited to a certain amount or less, but MnS has a lubricant effect within a certain range. Furthermore, as a result of intensive research by the present inventors, it has been revealed that a small amount of MnS has the effect of improving seizure resistance. On the other hand, if the S content is high, the material becomes brittle. Therefore, the S content is limited to 0.001% or more and 0.050% or less. The S content is preferably 0.002% or more and 0.040% or less.

[0033] In addition, the present invention is characterized in that the contents of C, Cr, Mo, V, and W are within the above-mentioned ranges, and in addition, the following formula (1) and formula (2) are satisfied. 0.6≦([%Mo]+[%W]) / ([%V]+[%Cr])≦4.0 (1) 1.0≦[%C]×([%Mo] / [%W])≦15.0 (2)

[0034] In the above formulas (1) and (2), [%C], [%Cr], [%Mo], [%V], and [%W] represent the content (mass%) of each element.

[0035] Regarding (([%Mo]+[%W]) / ([%V]+[%Cr])) in formula (1), this parameter indicates the ratio between the content of elements forming M2C carbides (Mo, W) and the content of elements forming other crystallized carbides (V, Cr). By adjusting the content of each element so as to satisfy formula (1), the proportion of crystallized M2C carbides can be optimized, and the seizure resistance and slip resistance of the outer layer material can be improved. If the lower limit of the above ratio is less than 0.6, the proportion of crystallized M2C carbides will be insufficient, and seizure resistance will decrease, and it may not be possible to achieve compatibility with slip resistance. On the other hand, if the upper limit of the above ratio exceeds 4.0, the proportion of M2C carbides crystallized in a planar and lamellar shape may become too high. If such a situation occurs, stress will concentrate on the M2C carbides with low toughness, making it easier for cracks to occur due to the M2C carbides. Therefore, the value of the above-mentioned ratio is limited to 0.6 or more and 4.0 or less, and preferably 0.8 or more and 3.5 or less.

[0036] Regarding ([%C]×([%Mo] / [%W])) in formula (2), this parameter indicates the amount of crystallized M2C carbide. By adjusting the content of each element so as to satisfy formula (2), the amount of crystallized M2C carbide can be optimized, and seizure resistance and slip resistance can be improved. In addition, if the lower limit of formula (2) is less than 1.0, the amount of crystallized M2C carbide may be insufficient, and seizure resistance may decrease. On the other hand, if the upper limit of formula (2) exceeds 15.0, the amount of crystallized M2C carbide may be excessive. In that case, cracks caused by M2C carbide are likely to occur. Therefore, the value of formula (2) is limited to 1.0 or more and 15.0 or less. It is preferable that the value of formula (2) is 2.5 or more and 12.5 or less.

[0037] Remainder: Fe and unavoidable impurities The balance other than the above-mentioned components consists of Fe and inevitable impurities. Examples of inevitable impurities include Mg, Zr, REM (rare earth metals), Sn, As, Sb, Bi, Pb, Zn, N, and O. However, within a range that does not impair the effects of the present invention, Mg, Zr, and REM may each be contained in an amount of 0.03% or less, Sn, As, and Sb in an amount of 0.04% or less, and Bi, Pb, Zn, N, and O in an amount of 0.01% or less. The above-mentioned REM is a general term for a total of 17 elements including Sc, Y, and lanthanoid elements. One or more of these 17 elements may be contained as inevitable impurities, and the REM content means the total content of these elements.

[0038] (Structure of outer layer material for hot rolling rolls) Next, the reason for limiting the structure of the hot rolling roll outer layer material of the present invention will be described. From past research results, it is known that in the hot rolling roll outer layer material, the larger the area ratio of crystallized carbides, the more the seizure resistance tends to improve. However, the larger the area ratio of crystallized carbides, the more likely slippage occurs in the hot rolling composite roll having the hot rolling roll outer layer material during rolling. The range of the crystallized carbide area ratio that maintains excellent seizure resistance and is less likely to cause slippage has not yet been clarified. Therefore, the present inventors have found the following as a result of intensive research.

[0039] The outer layer material for hot rolling rolls of the present invention is characterized in that it has a component composition in the above-mentioned range, and that all crystallized carbides are present at an area ratio of 6.0 to 18.0%, and that crystallized M2C type carbides are present at an area ratio of 1.0 to 8.0%. Here, all crystallized carbides refer to crystallized MC type carbides, crystallized M2C type carbides, and crystallized M7C3 type carbides. The matrix structure of the outer layer material is preferably martensite and / or bainite. In order to set the crystallized carbides to an appropriate area ratio and proportion, the outer layer material is limited to a structure having a component composition in the above-mentioned range, and that all crystallized carbides are present at an area ratio of 6.0 to 18.0%, and that crystallized M2C type carbides are present at an area ratio of 1.0 to 8.0%. It has been discovered that by doing so, the seizure resistance and slip resistance of the outer layer material for hot rolling rolls of the present invention are improved. The present invention is also characterized in that the area ratio of all crystallized carbides and the area ratio of M2C type carbides are within the above ranges, and further satisfy the following formula (3). 0.10≦Crystallized M2C type carbide area ratio (%) / total crystallized carbide area ratio (%)≦0.60 (3)

[0040] Formula (3) shows the relationship between the area ratio of all crystallized carbides and the area ratio of M2C type carbides, that is, the ratio of the area ratios. If the lower limit of formula (3) is less than 0.10, the amount of M2C type carbides or the ratio of M2C type carbides in all crystallized carbides may be insufficient, and the seizure resistance of the outer layer material may decrease. On the other hand, if the upper limit of formula (3) exceeds 0.60, the amount of M2C type carbides or the ratio of M2C type carbides in all crystallized carbides may be excessive. In that case, the seizure resistance decreases, and furthermore, cracks caused by M2C type carbides are more likely to occur. Therefore, the above-mentioned ratio is limited to 0.10 or more and 0.60 or less. It is preferable that the above-mentioned ratio is 0.20 or more and 0.50 or less.

[0041] Contrary to conventional knowledge, even if the area ratio of all crystallized carbides is small, when the area ratio of M2C type crystallized carbides is appropriate, the form of the crystallized planar M2C type carbides contributes to improving the seizure resistance. In addition, by suppressing the area ratio of all crystallized carbides, a significant decrease in the surface roughness of the outer layer material is prevented, and slippage is less likely to occur.

[0042] (Method of manufacturing outer layer material for hot rolling roll) Next, one embodiment of the method for producing the hot rolling roll outer layer material of the present invention will be described. When producing the hot rolling roll outer layer material of the present invention, a molten metal having the above-mentioned composition of the hot rolling roll outer layer material is poured into a rotating mold whose inner surface is covered with a refractory material mainly made of zircon or the like to a thickness of 1 to 5 mm, so as to have a predetermined thickness, and centrifugal casting is performed. Note that, as described above, the method for producing the hot rolling roll outer layer material by centrifugal casting corresponds to the method for producing the hot rolling roll outer layer material of the present invention.

[0043] In the case where the outer layer material of the hot rolling composite roll of the present invention is cast by a centrifugal casting method, the hot rolling composite roll has a centrifugally cast outer layer (hot rolling roll outer layer material) and an inner layer fused and integrated with the outer layer. An intermediate layer may be disposed between the outer layer and the inner layer. That is, the hot rolling composite roll of the present invention may be a hot rolling composite roll having three layers, that is, an intermediate layer fused and integrated with the outer layer, and an inner layer fused and integrated with the intermediate layer, instead of the inner layer fused and integrated with the outer layer. The inner layer is preferably produced by a static casting method.

[0044] For the inner layer to be statically cast, it is preferable to use spheroidal graphite cast iron, worm-shaped graphite cast iron (CV cast iron), or the like, which has excellent castability and mechanical properties. In a centrifugally cast roll, the outer layer and the inner layer are integrated by welding, and components of the outer layer material are mixed into the inner layer during the welding. If carbide-forming elements such as Cr and V contained in the outer layer material are mixed into the inner layer, the inner layer becomes weak. For this reason, it is preferable to suppress the mixing of the outer layer components into the inner layer as much as possible.

[0045] In addition, when forming an intermediate layer, it is preferable to use graphite steel, high carbon steel, hypoeutectic cast iron, etc. as the intermediate layer material. The intermediate layer and the outer layer are integrated by welding, and the components of the outer layer material are mixed into the intermediate layer during welding. When the intermediate layer containing the components of the outer layer material is welded to the inner layer, the components of the outer layer material mixed into the intermediate layer move to the inner layer. Therefore, in order to suppress the mixing of the components of the outer layer material into the inner layer, it is preferable to suppress the mixing of the components of the outer layer material into the intermediate layer as much as possible. There are various methods for suppressing the mixing of the components of the outer layer material into the intermediate layer, and one example is optimizing the pouring temperature and the pouring timing.

[0046] As a target structure in the outer layer (outer layer material of hot rolling roll) constituting the hot rolling composite roll, it is preferable that the total crystallized carbides are present in an area ratio of 6.0 to 18.0%, and the crystallized M2C type carbides are present in an area ratio of 1.0 to 8.0%. For this purpose, casting is performed so as to satisfy the following formula (4) which expresses the relationship between ΔT (pouring temperature-liquidus temperature) and the pouring time. Here, the pouring temperature refers to the temperature of the molten metal immediately before pouring into the mold. Also, the pouring time refers to the time required to complete pouring of the entire amount of molten metal into the mold. The mold temperature is preferably 250°C or less. 0.3℃ / sec≦ΔT(Pouring temperature ℃-Liquidus temperature ℃) / Pouring time sec≦5.0℃ / sec (4)

[0047] If the lower limit of formula (4) is less than 0.3°C / sec, the cooling rate during solidification (sometimes referred to as the casting rate) becomes too fast, so the grain size of the crystallized carbide becomes smaller than when the cooling rate is slow. As a result, the total amount of crystallized carbide in the outer layer material becomes insufficient. On the other hand, if the upper limit of formula (4) exceeds 5.0°C / sec, the cooling rate during solidification becomes too slow, so the grain size of the crystallized carbide becomes larger than when the cooling rate is fast. As a result, the total amount of crystallized carbide in the outer layer material becomes excessive. Therefore, the value of formula (4) is limited to 0.3°C / sec or more and 5.0°C / sec or less. In addition, the value of formula (4) is preferably 0.4°C / sec or more, more preferably 0.5°C / sec or more. In addition, the value of formula (4) is preferably 4.5°C / sec or less, more preferably 4.0°C / sec or less. The value of formula (4) is preferably 0.4° C. / sec or more and 4.5° C. / sec or less, and more preferably 0.5° C. / sec or more and 4.0° C. / sec or less.

[0048] The ΔT (pouring temperature °C-liquidus temperature °C) described in the above formula (4) will be explained. ΔT (pouring temperature-liquidus temperature) indicates the temperature range until the start of solidification. By using this parameter, it is possible to precisely control the period from pouring to the start of solidification. That is, in the past, regardless of the thermal properties (liquidus temperature) of the material, the casting conditions, i.e., the casting speed, were managed using "pouring temperature / pouring time". Therefore, in the past, there was a possibility that the casting temperature and the casting time could not be controlled according to each material. In contrast, in this embodiment, the casting conditions, i.e., the cooling rate, are managed using "ΔT (pouring temperature-liquidus temperature) / pouring time". Therefore, the thermal properties (liquidus temperature) of each material can be taken into consideration in managing the cooling rate, and the casting temperature and the casting time can be controlled according to each material. A method for determining the liquidus temperature will be explained. The liquidus temperature was measured by heating a sample (φ5×5mm) cut from the center of the thickness of the outer layer material using an ULVAC-RIKO differential thermogravimetric analyzer (TGD-9800) from 1000°C to 1530°C, and then cooling it from 1530°C to 1000°C. An alumina container was used as the measurement container, and the heating rate was set to 5°C / min, and the experiment was performed in an Ar atmosphere. The liquidus temperature of the sample cut from the center of the thickness of the outer layer material was measured by differential thermal analysis (DTA measurement). The liquidus temperature was measured for each of the three samples, and the average value was used as the liquidus temperature.

[0049] The heat treatment is preferably performed at least once by heating the outer layer material to 900 to 1100°C and then cooling it with air or air blast cooling. Furthermore, it is preferable to perform tempering treatment two or more times by holding the outer layer material at a temperature and then cooling it so that the tempering parameter P described in the following formula (5) is within the range of 13,000 to 18,000. At this time, the above-mentioned structure can be easily obtained by changing the quenching temperature, tempering parameter, and number of tempering times within the ranges described depending on the components. P = T (log(t) + A) (5) Here, T is the tempering temperature (K), t is the tempering time (h), and A is a constant (A=20 in the present invention).

[0050] As a result of the above, a composite roll for hot rolling having three layers, that is, an outer layer, an intermediate layer, and an inner layer, or two layers, that is, an outer layer and an inner layer, can be obtained.

[0051] (Tissue Observation Method) Next, the observation method of the structure of the outer layer material will be described below. First, a plurality of samples of the outer layer material obtained by the above-mentioned manufacturing method were prepared. Each sample was taken from the center of the thickness of the outer layer material obtained by the above-mentioned manufacturing method. Each sample was mirror-polished, and the polished surface of the outer layer material was corroded with a nital solution. Then, the exposed structure of the outer layer material was observed with a digital microscope (magnification 200 times). In addition, the exposed structure of the outer layer material was photographed, and the area ratio of all crystallized carbides on the polished surface of the outer layer material was measured by image analysis. Then, using an image analysis tool (ImageJ), a binarization process was performed on the photograph of the polished surface at a measurement magnification of 200 times. This is because there is a difference in brightness between the base structure and the crystallized carbides in the photograph, and by performing binarization processing, the base structure and the crystallized carbides can be classified and their respective areas can be obtained. Ten photographs were taken of the polished surface of each sample, and the average area ratio of all crystallized carbides was calculated for each sample, taking the entire photographed image (roll structure) as 100%.

[0052] In addition, to calculate the area ratio of the crystallized M2C type carbides, the crystal orientation of the crystallized carbides and the crystal orientation of the matrix were measured using SEM-EBSD with the samples used for observing the structure. Then, the images of the crystallized M2C type carbides were separated by utilizing the differences in each crystal structure. The measurement conditions for SEM-EBSD were an acceleration voltage of 15 kV, a measurement magnification of 200 times, a measurement range of 600 × 1100 μm, and a step size of 0.5 μm. The crystal orientation of the crystallized M2C type carbides was analyzed using a Mo2C database in the software owned by TSL. For the rest, Iron (alpha) was used as the crystal orientation of the matrix structure, and Iron (gamma) was used as the crystal orientation of the MC type carbides. The area ratio of only the crystallized M2C type carbides was measured using an image analysis tool (ImageJ).

[0053] In addition, the hardness of the hot rolling roll outer layer material of the present invention is preferably 44.0HS or more and 52.0HS or less in Shore hardness at 600 ° C. and 74.0HS or more and 86.0HS or less in Shore hardness at 20 ° C. The roll surface temperature during hot rolling is about 600 ° C., and if the Shore hardness at 600 ° C. is less than 44.0HS, plastic flow occurs and the steel material is likely to seize on the roll surface. On the other hand, if the hardness exceeds 52.0HS, the roll hardness is too high and slippage is likely to occur during rolling. Such hardness can be stably ensured by heat treating the roll having the composition of the present invention so that the tempering parameter P described later is within the range of 13000 to 18000. EXAMPLES

[0054] The present invention will be described in more detail with reference to the following examples, which are not intended to limit the scope of the present invention.

[0055] The chemical compositions of the test materials of the present invention and the comparative examples are summarized in Table 1. The molten metal having the composition of the outer layer material of the hot rolling roll shown in Table 1 was melted in a high-frequency melting furnace, and a ring-shaped test material (outer diameter: φ250 mm, width: 65 mm, thickness: 55 mm) was produced by centrifugal casting so as to satisfy the above formula (4). The balance other than the composition shown in Table 1 is Fe and unavoidable impurities. In Table 1 and Table 2 described later, the ring-shaped test material is simply described as the test material. Next, after cooling, the ring-shaped test material was removed from the mold and quenched at 900 to 1100 ° C. Then, the ring-shaped test material was heated and held, and then cooled, and tempered three times so that the tempering parameter P expressed by the above formula (5) was within the range of 13000 to 18000. Then, for each of the ring-shaped test pieces, microstructure observation, measurement of the seizure area ratio using a drop-weight frictional thermal shock tester, crack evaluation, and friction coefficient measurement using a hot rolling wear tester were performed. Note that the test pieces for the microstructure observation, the drop-weight frictional thermal shock test, and the hot rolling wear test were each taken from the center in the length direction of each ring-shaped test piece and the center in the plate thickness direction (hereinafter referred to as the thickness center).

[0056] [Table 1]

[0057] The friction coefficient was measured using a hot rolling wear tester as follows. FIG. 1 is a diagram for explaining the position where test pieces for hot rolling wear tests were taken from the ring-shaped test material. As shown in FIG. 1, a ring-shaped test piece (outer diameter 60 mmφ, width 10 mm, with C1 chamfer) 1 for hot rolling wear tests was taken from the center in the length direction of the ring-shaped test material TM of each of the present invention examples and each of the comparative examples, and from the center of the wall thickness. C1 chamfering means that the corner of the test piece is cut off at an angle of 45° at a position 1 mm inward from the corner of the test piece.

[0058] The hot rolling wear test was performed by a two-disk sliding rolling method between a test piece 1 and a mating piece 4, as shown in FIG. 2. The test piece 1 was rotated at 76 rpm while being cooled with cooling water 2. The test piece 1 and the mating piece 4 (outer diameter 190 mmφ, width 15 mm, C1 chamfer) heated to 1000°C by a high-frequency induction heating coil 3 were brought into contact with the rotating test piece 1 under a load of 686 N, and the test piece 1 and the mating piece 4 were rolled under the condition of a slip ratio of 10%. The direction of the line of action of the load described above is shown by reference numeral 7 in FIG. 2. The rotation direction of the test piece 1 is shown by reference numeral 5 in FIG. 2, and the rotation direction of the mating piece 4 is shown by reference numeral 6 in FIG. 2. In the example shown in FIG. 2, the rotation direction 5 of the test piece 1 and the rotation direction 6 of the mating piece 4 are opposite to each other, so that the test piece 1 rotates clockwise and the mating piece 4 rotates counterclockwise.

[0059] In addition, the mating piece 4 was replaced with a new one every hour, and the hot rolling wear test was performed again. This was repeated a total of five times, and the hot rolling wear test of the test piece 1 was performed for a total of five hours. The torque and load during the test were measured, and the friction coefficient was calculated from the following formula (5). In addition, the ratio of the average value of the friction coefficients obtained in the first test, i.e., the first hour of the hot rolling wear test, for one minute immediately before the end of the test to the average value of the friction coefficients obtained in the fifth test, i.e., the last hour of the hot rolling wear test, for one minute immediately before the end of the test was calculated. For each sample (test piece 1), two sets of hot rolling wear tests for a total of five hours were performed, and the average value of the above-mentioned ratios obtained in each hot rolling friction test was calculated. The hot rolling wear test was performed twice for each sample. μ = T / P × L (5) Here, μ is the friction coefficient, T is the torque of test piece 1 (kgf m), P is the load (kgf), and L is the radius of the test piece (m).

[0060] The seizure resistance evaluation using the drop-weight frictional thermal shock test was performed as follows. Using the drop-weight frictional thermal shock tester shown in FIG. 3, the seizure test was performed four times for each test piece. A rectangular test piece (22×30×23 mm, test surface: 22×30 mm) 11 for the drop-weight frictional thermal shock test was taken from the center in the length direction and the center of the wall thickness of each of the ring-shaped test pieces of the present invention examples and each of the comparative examples. That is, although not shown in detail, the test piece for the drop-weight frictional thermal shock test was taken from the ring-shaped test piece in the same manner as the test piece for the hot rolling wear test was taken from the ring-shaped test piece shown in FIG. 1. In the drop-weight frictional thermal shock tester, a weight 8 shown in FIG. 3 is dropped onto a rack 9 to push the rack 9 downward and rotate a pinion 10 meshing with the rack 9. Since the mating piece 12 is attached to the pinion 10, when the pinion 10 rotates, the mating piece 12 rotates (revolves) around the central axis of rotation of the pinion 10. In this way, the mating material 12 is strongly rubbed against the test piece 11. This seizure test leaves an indentation on the test piece 11, and the mating piece 12 seizes and adheres to a part or the entirety of the indentation. The area of ​​the test piece 11 where the mating piece 12 seized and adhered (hereinafter referred to as the seizure area) was measured. In addition, the area (hereinafter referred to as the indentation area) of the indentation (hereinafter referred to as the indentation portion) formed on the test piece 11 was measured.

[0061] The above-mentioned seizure test was performed four times for each ring-shaped test material, and the seizure area and the indentation area were measured for each seizure test. The seizure area was divided by the indentation area to calculate the seizure area ratio (%). The average value of the seizure area ratio of the four seizure tests was then calculated. The smaller the seizure area ratio, the better the seizure resistance. After the seizure test, the test surface of the test piece 11 was observed with a digital microscope to check for the presence or absence of cracks in the indentation. If cracks were found in even one of the four tests, it was determined that there were cracks. The results of the hot rolling wear test and the seizure test are summarized in Table 2.

[0062] [Table 2]

[0063] The test results were evaluated as follows: A seizure area rate of 42.0% or less was rated as "pass" (i.e., excellent seizure resistance), and a rate of more than 42.0% was rated as "fail." Additionally, a friction coefficient ratio (μ5th / μ1st) of 0.80 or more was rated as "pass" (i.e., excellent slip resistance), and a rate of less than 0.80 was rated as "fail."

[0064] As is clear from Table 2, it was confirmed that the present invention example had both excellent seizure resistance and slip resistance compared to the comparative example. In addition, in the present invention example, the casting conditions, i.e., the cooling rate, are controlled using "ΔT (pouring temperature - liquidus temperature) / pouring time". Therefore, the thermal properties (liquidus temperature) of each material can be taken into consideration in controlling the cooling rate, and the pouring temperature and pouring time can be controlled according to each material. The following will be explained by comparing test materials No. 12 and No. 26, which have the same components. As shown in Table 2, the characteristics of test material No. 26, whose casting conditions do not satisfy the appropriate values, i.e., the above-mentioned formula (4), such as the total crystal carbide area ratio (%) and the friction coefficient ratio in the hot rolling test, are inferior to those of test material No. 12, whose casting conditions satisfy the appropriate values.

[0065] Therefore, according to the present invention, it is possible to manufacture a hot rolling roll outer layer material and a hot rolling composite roll that are excellent in galling resistance and slip resistance. As a result, it is possible to improve the life of the hot rolling roll outer layer material and the hot rolling composite roll, and to reduce interruptions and time losses in rolling due to roll troubles. This also makes it possible to improve the rolling efficiency and the productivity of hot rolled steel sheets. [Explanation of symbols]

[0066] 1. Hot rolling wear test specimen 2 Cooling water 3 High frequency induction heating coil 4. Mating piece for hot rolling wear test 5. Rotation direction of test piece 6 Rotation direction of the mating piece 7 Load acting line direction 8 weight 9. Rack 10 Pinion 11 Test piece for drop weight friction thermal shock test 12 Counterpart for drop weight friction thermal shock test TM Ring-shaped test material

Claims

1. In mass percent, Contains C: 1.1 to 2.5%, Si: 0.1 to 3.5%, Mn: 0.1 to 3.5%, Ni: 0.5 to 6.5%, Cr: 1.5 to 6.5%, Mo: 2.5 to 18.0%, V: 1.5 to 6.5%, W: 0.5 to 3.5%, P: 0.01 to 0.08%, S: 0.001 to 0.050%, and The balance is Fe and unavoidable impurities. The contents of Cr, Mo, V, and W satisfy the following formula (1), The contents of C, Mo, and W satisfy the following formula (2), The area ratio of all crystallized carbides is 6.0 to 18.0%; Crystallization M 2 The area ratio of C-type carbides is 1.0 to 8.0%; Area ratio of total crystallized carbides and crystallization M 2 A hot rolling roll outer layer material, the relationship with an area ratio of C-type carbides satisfying the following formula (3): 0.6≦([%Mo]+[%W]) / ([%V]+[%Cr])≦4.0...(1) 1.0≦[%C]×([%Mo] / [%W])≦15.0 (2) 0.10≦Crystal Out M 2 Area ratio of C-type carbides (%) / area ratio of all-crystalline carbides (%) ≦ 0.60 ・・・(3) In formula (1) and formula (2), [%C], [%Cr], [%Mo], [%V], and [%W] are the contents (mass%) of each element.

2. A method for producing an outer layer material for a hot rolling roll according to claim 1, A method for producing an outer layer material for a hot rolling roll, the method comprising: pouring a molten metal of the outer layer material having the above-mentioned component composition into a mold while rotating the mold, thereby generating centrifugal force in the molten metal poured into the mold; and using the centrifugal force to bring the molten metal into close contact with the mold, thereby centrifugal casting the outer layer material for a hot rolling roll, the method satisfying the following formula (4): 0.3° C. / sec≦ΔT (pouring temperature (° C.)−liquidus temperature (° C.)) / pouring time (sec)≦5.0° C. / sec (4)

3. A composite roll for hot rolling having a two-layer structure of an outer layer and an inner layer, or a three-layer structure of an outer layer, an intermediate layer, and an inner layer, 2. A composite roll for hot rolling, wherein the outer layer comprises the outer layer material for hot rolling roll according to claim 1.

Citation Information

Patent Citations

  • Rolling roll and its manufacture

    JP1994025794A

  • Roll for rolling

    JP1994145888A

  • Roll for hot rolling

    JP1996165544A

  • Roll outer layer material for hot rolling and compound roll for hot rolling

    JP2018161655A

  • Roll outer layer for hot rolling and composite roll for hot rolling

    JP2023178732A